Effects of climate on the solar-powered R1234ze/CO2 cascade cycle for space cooling. (June 2020) - Li, Hao; Gong, Xiufeng; Xu, Wenjie; Li, Minxia; Dang, Chaobin
Abstract: In order to promote refrigerant substitution by CO2 for space cooling, and to relieve the requirement of large collector area in the solar-powered ejector refrigeration system, a solar-powered R1234ze/CO2 cascade refrigeration system was proposed. A theoretical investigation was conducted to estimate the effects of cooling load and solar radiation resources in four cities to denote the influence of the climate on the cascade system. Firstly, the performance of the proposed cascade system was analyzed. Secondly, the effects of solar collector area were illustrated. In comparison with the conventional solar-powered ejector cycle at the given operating conditions, the power consumption of the cascade system is far less when the collector area is lesser. Then the analysis was conducted when the cascade system was applied to different locations. With the increase of the cooling load, the power consumption of the cooling system increases, and the power saving potential increases. Further, the ratio of solar irradiance to cooling load was proposed as criteria for different locations. With the increase of the ratio, collector area needed in the cascade system decreases. And the higher the ratio, the smaller difference of the energy saving potentials between the cascade system and ejection system is. Highlights: A solar-powered R1234ze/CO2 cascade cycle was proposed. The performance of CO2 refrigeration system was improved by applying the ejector and cascade cycle. The comparison of the cascade cycle with solar ejection cycle was conducted. The effects of climates on system performance were analyzed.